The Corellation of Nurse's Workload with Quality of Nursing Care Documentation - Safaruddin; Supriadi; Abd Kadir (Formosa Journal of Science and Technology, 2023)
Documentation of nursing care is a means of communication between health workers in the context of restoring patient health. In this study, the type of quantitative researcher with an analytic study and with a cross-sectional design where they wanted to know the relationship between the workload of nurses and the quality of nursing care in class III inpatient rooms at RSUD dr. Abdul Rivai Berau district. The population in this study were nurses in class III inpatient rooms, namely flamboyant, dahlia and bougenvile totaling 69 people with a total sample of 40 people. In this study the sampling technique used was non-probability sampling with purposive sampling technique. Purposive sampling is a sampling technique with certain considerations. Spearman's statistical test results for the ranking of the SPSS program obtained p value = 0.001 which is less than the p value, meaning that there is a relationship between nurse workload and quality of nursing care in class III inpatient rooms at RSUD dr. Abdul Rivai Berau district. So it can be concluded that there is a significant relationship between the workload of nurses and the quality of nursing care in class III inpatient rooms at RSUD dr. Abdul Rivai Berau district in 2022.